Simultaneous enrichment and sequential separation of glycopeptides and phosphopeptides with poly-histidine functionalized microspheres - Shang, Danyi; Chen, Cheng; Dong, Xuefang; Cui, Yun; Qiao, Zichun; Li, Xiuling; Liang, Xinmiao (Frontiers in Bioengineering and Biotechnology, 2022)
Protein phosphorylation and glycosylation coordinately regulate numerous complex biological processes. However, the main methods to simultaneously enrich them are based on the coordination interactions or Lewis acid-base interactions, which suffer from low coverage of target molecules due to strong intermolecular interactions. Here, we constructed a poly-histidine modified silica (Poly-His) microspheres-based method for the simultaneous enrichment, sequential elution and analysis of phosphopeptides and glycopeptides. The Poly-His microspheres driven by hydrophilic interactions and multiple hydrogen bonding interactions exhibited high selectivity and coverage for simultaneous enrichment of phosphopeptides and glycopeptides from 1000 molar folds of bovine serum albumin interference. Furthermore, “on-line deglycosylation” strategy allows sequential elution of phosphopeptides and glycopeptides, protecting phosphopeptides from hydrolysis during deglycosylation and improving the coverage of phosphopeptides. The application of our established method to HT29 cell lysates resulted in a total of 1601 identified glycopeptides and 694 identified phosphopeptides, which were 1.2-fold and 1.5-fold higher than those obtained from the co-elution strategy, respectively. The Poly-His based simultaneous enrichment and sequential separation strategy might have great potential in co-analysis of PTMs-proteomics of biological and clinic samples.